Aromatic‐Imide‐Based Thermally Activated Delayed Fluorescence Materials for Highly Efficient Organic Light‐Emitting Diodes. Issue 30 (23rd June 2017) - Li, Meng; Liu, Yanwei; Duan, Ruihong; Wei, Xiaofang; Yi, Yuanping; Wang, Ying; Chen, Chuan‐Feng
Abstract: Aromatic‐imide‐based thermally activated delayed fluorescence (TADF) materials with a twisted donor–acceptor–donor skeleton were efficiently synthesized and exhibited excellent thermal stability and high photoluminescence quantum yields. The small Δ E ST value (<0.1 eV) along with the clear temperature‐dependent delayed component of their transient photoluminescence (PL) spectra demonstrated their excellent TADF properties. Moreover, the performance of organic light‐emitting diodes in which TADF materialsAI‐Cz andAI‐TBCz were used as dopants were outstanding, with external quantum efficiencies up to 23.2 and 21.1 %, respectively. Abstract : No apologies for this delay : Thermally activated delayed fluorescence (TADF) materials with a twisted donor–acceptor–donor skeleton have been developed with an N ‐phenylphthalimide acceptor moiety (see structure). They exhibit small Δ E ST values (<0.1 eV) and excellent TADF properties. Organic light‐emitting diodes fabricated with these materials had a high external quantum efficiency of up to 21.1 and 23.2 %.